Racial/ethnic variations in the main and buffering effects of ethnic and nonethnic supports on depressive symptoms among five ethnic immigrant groups in Toronto. Issue 3 (3rd May 2016) - Kim, Il-Ho; Noh, Samuel
ABSTRACT: Objectives. This study examined variations in the main and buffering effects of ethnic and nonethnic social support on depressive symptoms associated with discrimination among five immigrant groups in Toronto. Design. Data were taken from the Toronto Study of Settlement and Health, a cross-sectional survey of adult immigrants from five ethnic communities (Vietnamese, Ethiopian, Iranian, Korean, and Irish) in Toronto. A total of 900 surveys were collected through face-to-face interviews conducted between April and September 2001. Results. Significant ethnic variations were observed in the effects of both ethnic and nonethnic social supports on discrimination-related depressive symptoms. Regarding the main effect, ethnic social support was significantly stronger for Iranian, Ethiopian, and Korean immigrants than for Irish immigrants. The benefits of nonethnic support were stronger for Iranian immigrants compared to the effect found in the Irish sample. With respect to stress- buffering or stress-moderating effects of social support, ethnic support was significant in all ethnic groups, except the Vietnamese group. Nonethnic support aggravated the negative impact of discrimination on depressive symptoms in the Irish group, but exerted a stress-buffering effect in the Iranian group. Conclusions. Overall, social supports received from fellow ethnic group members had significant main effects (suppressing depressive symptoms) and stress-buffering effects and were most pronounced in the minority ethnic immigrant groups of Ethiopians, Koreans, and Iranians. The effects were least evident among the Vietnamese and Irish. Evidence for the stress-suppressing and stress-buffering role of cross-ethnic group supports was unclear, and even inverted among Irish immigrants. Empirical evidence from the current study seems to support the sociocultural similarity hypothesis of social support.